2021
DOI: 10.3390/ma14071773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tensile Deformation on Residual Stress of GH4169 Alloy

Abstract: In order to reduce the residual stress of the GH4169 alloy, the effect and micro-mechanism of the tensile deformation were studied. The residual stress, dislocation density, and distribution of the GH4169 alloy were analyzed by X-ray residual stress tester, X-ray diffractometer (XRD), and electron backscatter diffraction (EBSD). The results show that: with the increase of tensile deformation, the residual stress relief first increases and then decreases. When the tensile deformation is 3%, the reduction rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…Figure 3 shows the influence of the FSA time on mechanical properties. From Figure 3 a, it can be found that there is no obvious elastic-plastic transition period, which is consistent with the normal behavior reported in References [ 42 , 43 , 44 ]. Thus, the offset yield strength corresponding to 0.2% plastic strain (called yield strength) is used.…”
Section: Results and Analysissupporting
confidence: 88%
“…Figure 3 shows the influence of the FSA time on mechanical properties. From Figure 3 a, it can be found that there is no obvious elastic-plastic transition period, which is consistent with the normal behavior reported in References [ 42 , 43 , 44 ]. Thus, the offset yield strength corresponding to 0.2% plastic strain (called yield strength) is used.…”
Section: Results and Analysissupporting
confidence: 88%